Evaluasi Praktik Asesmen Diagnostik IPA Untuk Mengidentifikasi Kesulitan Belajar Siswa Sekolah Dasar - Juryatina, Juryatina; Haris, Abdul; Uyun, Nurul; Ekahidayatullah, M. (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
Diagnostic assessment is a crucial component of the learning process to identify students’ understanding gaps from the outset. However, in elementary schools, its implementation is often limited to conventional written tests that do not fully reflect students' learning needs. This study aims to describe the implementation of diagnostic assessment in science learning for fifth-grade students at SDN Jala, Bima Regency. A qualitative descriptive method was employed, with data collected through observation, interviews, and documentation. Thematic analysis was used to uncover patterns and significant findings related to assessment practices. The results indicate that diagnostic assessments were conducted through oral questions and initial learning tasks, but not in a systematic or in-depth manner. Teachers tend to rely on general initial evaluations without using structured instruments to identify misconceptions or individual student needs. These findings highlight the need for teacher training and capacity building in designing and applying more effective diagnostic assessments. The results are essential as a basis for improving the quality of science learning through assessments that can accurately portray students’ readiness and understanding at the beginning of instruction.